Diferenciação vertical em um modelo de hotelling com firmas heterogêneas - Oliveira, Érica Diniz (2009)
This paper presents a duopolist model with heterogeneous firms (different marginal costs) and assimetric information about the vertical preferences of the consumers. We find that the asymmetry of information on the vertical dimension and the difference in costs greatly influences the pricing and the structures for market equilibrium. An important result arising from these two aspects is the existence of a mass of consumers that can buy from both firms. It is also observed that the greater the heterogeneity of costs, the greater the market power of the most efficient firm.